محاولات مدير كلية المعلمين الإسلامية في ترقية اللغة العربية لدى الطلاب في الصف الأول المتخصص بمعهد الكوثر باني تونجاه سومطرة الشمالية - Ade Muhammad Ritonga; Danang Prasetio; Fakhrurrozi Fakhrurrozi (Fakultas Tarbiyah Universitas Ibrahimy, 2022)
This study aims to determine the efforts of the director of Kulliyatul Muallimin Al Islamiyah (KMI) in developing Arabic language and administration of education in the intensive first grade of the modern Islamic boarding school Alkautsar Pane Tongah, North Sumatra. This study is a qualitative descriptive field research. Data was collected by means of interview observations and documentation. The results of this study are that among the efforts of the KMI chief in developing beginner Arabic level is to identify problems related to the development of Arabic by looking at the academic background of the students, then by adding Arabic lessons and placing special Arabic teachers in the beginner class, then by including Arabic subjects that help the development of the Arabic language. The efforts of the KMI director in education administration are by setting an Arabic curriculum and compiling an educational calendar.